Study of microbial flora in indwelling catheter, drains, CIVP lines and endotracheal tubes (Journal of Pathology of Nepal, 2013)
Background: The use of indwelling devices like Urinary catheter, Drain tubes, Central intravascular catheter, endotracheal tubes has become routine practice in the medical field. Localized or systematic infection are frequent complications associated with extensive use of these devices, requiring its removal or may even be associated with life threatening consequences. Materials and Methods: Microbiological study was carried out among all the indwelling device samples received from 20th April 2011 to 19th April 2012 at Clinical Microbiology Laboratory, Department of Pathology, Kathmandu Medical College Teaching Hospital. Results: Out of total 205 samples (125 Foley’s catheters, 31 drain tubes, 29 central intravascular catheter lines and 20 endotracheal tubes) received during this study period, 38.4% urinary catheters, 23.33% drain tubes, 6.9% central intravascular catheter lines and 40.0% endotracheal tubes were found to have significant growth. Escherichia coli and Klebsiella were found to be the commonest organisms. Conclusion: The infection rates of indwelling devices used for various reasons are found to be very high. These infections have increased the morbidity and mortality of the hospitalized patients and also increased the duration of hospital stay. Thus aseptic measurements during insertion of these devices periodic change of these devices may help to overcome these complications. DOI: http://dx.doi.org/10.3126/jpn.v3i6.8995   Journal of Pathology of Nepal (2013) Vol. 3, 469-471